The development and application of a scuffing test based on contra-rotation - Peng,B; Spikes,H; Kadiric,A (Tribology Letters, 2019)
Scuffing is a surface failure mode that occurs in sliding–rolling contacts subjected to high loads and high sliding speeds, such as those in gears and cam-followers. Owing to its sudden onset, rapid progression and dependence on both fluid and boundary lubricant films, scuffing is difficult to study in a repeatable manner. This paper describes further development of a recently proposed scuffing test method based on contra-rotation, its extension to higher loads using a new experimental set-up and its application to study the onset of scuffing with a selection of model and fully-formulated oils. The method employs two surfaces moving in opposite directions under rolling–sliding conditions, with a fixed load and step-wise increasing sliding speed. By decoupling the entrainment and sliding speeds, the method allows the effects of lubricant formulation on scuffing performance to be isolated from the influence of viscosity. The approach achieves high sliding speeds in parallel with low entrainment speeds, while minimising the undesirable effects of surface wear and frictional heating. The proposed test is relatively fast and economical, with total test time of about 30 min including specimen cleaning and set-up. Results show that the newly implemented modifications have improved the repeatability of the test method, so that the number of repeat tests required for reliable oil ranking results is minimal. Tests with model and fully-formulated oils show that the onset of scuffing is characterised by a sharp and unrecoverable increase in friction and accompanied by the destruction of any boundary films. All tests show that the relationship load × speedn = constant holds at scuffing, with the exact value of the exponent n being dependent on the oil formulation. Additivised oils were shown to have enhanced scuffing resistance, which arises from their ability to postpone the uncontrollable rise in friction to higher sliding speeds. Finally, the critical maximu